Blunted superior temporal gyrus activity to negative emotional expression after mindfulness-based cognitive therapy for late-life depression - Liu, Weijian; Li, Hui; Lin, Xiao; Li, Peng; Zhu, Ximei; Su, Sizhen; Shi, Jie; Lu, Lin; Deng, Jiahui; Sun, Xinyu (Frontiers in Aging Neuroscience, 2022)
Facial emotion recognition plays an important role in social functioning. Patients with late-life depression (LDD) often have abnormal facial emotion recognition. Mindfulness-based cognitive therapy (MBCT) is beneficial in treating depression. This study examined whether MBCT can act as an effective augmentation of antidepressants and improve facial emotion recognition in patients with LLD and its underlying neural mechanism. Patients with LLD were randomized into two groups (n = 30 per group). The MBCT group received an eight-week MBCT in conjunction with stable medication treatment. The other group was treated as usual (TAU group) with stable medication treatment. The positive affect (PA) scale, negative affect (NA) scale, and facial emotion recognition task with an fMRI scan were performed before and after the trial. After eight weeks of treatment, the repeated ANOVA showed that the PA score in the MBCT group significantly increased (F(1,54) = 13.31, p = 0.001), but did not change significantly (F(1,54) = 0.58, p = 0.449) in the TAU group. The NA scores decreased significantly in both the MBCT group (F(1,54) = 19.01, p < 0.001) and the TAU group (F(1,54) = 16.16, p < 0.001). Patients showed an increase in both recognition accuracy and speed of angry and sad faces after eight weeks of MBCT. No improvement was detected in the TAU group after treatment. A significant interaction effect was found in the change of activation of the left superior temporal gyrus (L-STG) to negative emotional expression between time and groups. Furthermore, a decrease in activation of L-STG to negative emotional expression was positively correlated with the increase in PA score. The MBCT is beneficial for improving affect status and facial emotion recognition in patients with LLD, and the L-STG is involved in this process.